I AM CHANG-BEK, I AM AN ADYGHE.... (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the origin, etymology and historical sources associated with the ethnonym Adygine - the name of the largest tribal group within the Kyrgyz people. Information about the etymology, semantics and origin of the ethnonym Adygine is very rare in the scientific literature. The origin of the ethnonym of the largest ethnic group of the Kyrgyz is considered to be the mountainous and forested regions of Southern Siberia, one of the ethnic historical homelands of the Kyrgyz. The meaning and etymology of the tribal names that are part of the Adygine tribal group - börü, bargy, zhoru, karabagysh, sarttar - are totemic in nature. Ethnonyms obviously come from the names of birds and wild animals. It is known that parallels of the ethnonym are found among the Tuvinians and Khakassians, descendants of the Yenisei Kirghiz, in the forms adyk, adyk-tulush. The ethnonym “adyk” has retained its ancient lexical form and meaning. The name of the tribal group “Adygine” can be directly related to the “bear”, a well-known totem common among the peoples of the world since ancient times.
Keywords: Kyrgyz, Adygin, tribe, ethnogenesis, etymology, Minus, totem.